How Do Health Literacy, Numeric Competencies, and Patient Activation Relate to Transition Readiness in Adolescents and Young Adults With Rheumatic Diseases?. Issue 9 (10th August 2019) - Lazaroff, Samuel M.; Meara, Alexa; Tompkins, Mary Kate; Peters, Ellen; Ardoin, Stacy P.
Abstract : Objective: To evaluate how demographics, health literacy, numeracy, and patient activation are related to transition readiness in adolescent and young adult (AYA) patients and to describe how parent/guardian (PG) performance on these metrics predicts AYA patients' transition readiness. Methods: In this single center, cross‐sectional study, consecutive English‐speaking AYA patients ages 17–21 years and PGs were recruited from outpatient rheumatology clinics. Participants completed the following self‐reported instruments: demographic questionnaire, Short Test of Fundamental Health Literacy, Objective Numeracy Scale, Subjective Numeracy Scale, Symbolic‐number mapping, Patient Activation Measure, and Transition Readiness Assessment Questionnaire (TRAQ; AYA patients only). Results: Ninety‐one AYA patients participated in the study, of whom 64 of 91 (70%) had juvenile idiopathic arthritis, and 54 PGs. Mean ± SD TRAQ score was 4.0 ± 0.65, correlating with "I am starting to do this" stage of change. Most participants (98%) had adequate health literacy. Multivariable regression analysis showed that AYA patients of female sex, older age, and higher patient activation significantly predicted higher TRAQ scores ( P < 0.05). No PG characteristics were linked to higher AYA patient TRAQ scores. Conclusions: Transition readiness in AYA patients as measured by TRAQ is associated with female sex, older age, and higher patient activation. Though sex and age are nonmodifiable, interventions to boost patient activation represent a promising opportunity to improve transition readiness and outcomes.